Extended Mortality and Chronic Kidney Disease After Septic Acute Kidney Injury. (June 2020) - Chua, Horng-Ruey; Wong, Weng-Kin; Ong, Venetia Huiling; Agrawal, Dipika; Vathsala, Anantharaman; Tay, Hui-Ming; Mukhopadhyay, Amartya
Purpose: To evaluate 1-year mortality in patients with septic acute kidney injury (AKI) and to determine association between initial AKI recovery patterns ( reversal within 5 days, beyond 5 days but recovery, or nonrecovery ) and chronic kidney disease (CKD) progression. Methods: Prospective observational study, with retrospective evaluation of initial nonconsenters, of critically ill patients with septic AKI. Results: We studied 207 patients (age, mean [SD]: 64 [16] years, 39% males), of which 56 (27%), 18 (9%), and 9 (4%) died in intensive care unit (ICU), post-ICU in hospital, and posthospitalization, respectively. Infections (including pneumonia) and major adverse cardiac events accounted for 64% and 12% of deaths, respectively. Factors independently associated with 1-year mortality include older age, ischemic heart disease, higher Simplified Acute Physiology Score II, central nervous system or musculoskeletal primary infections, higher daily fluid balance (FB), and frusemide administration during ICU stay (all P < .05). Among 63 patients receiving renal replacement therapy (RRT), hospital mortality was higher with cumulative median FB >8 L versus ≤8 L at RRT initiation (57% vs 24%; P = .009); there was trend for less ICU- and RRT-free days at day 28 in patients with higher FB pre-RRT ( P = NS). Chronic kidney disease progression over 1 year developed in 21%, 30%, and 79% of 105 initial survivors with AKI reversal, recovery, and nonrecovery, respectively ( P < .001). Acute kidney injury nonrecovery during hospitalization independently predicted CKD progression ( P = .001). Conclusions: Patients with septic AKI had 40% 1-year mortality, mainly associated with infections. High FB and frusemide administration were modifiable risk factors. Risk of CKD progression is high especially with initial AKI nonrecovery.